2010
DOI: 10.1097/pas.0b013e3181d94d53
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Adenocarcinoma of Fundic Gland Type (Chief Cell Predominant Type): Proposal for a New Entity of Gastric Adenocarcinoma

Abstract: Only a few cases of gastric adenocarcinoma of fundic gland type have been reported. Gastric adenocarcinoma with chief cell differentiation (GA-CCD) has been recently reported as a new variant of gastric adenocarcinoma. However, its clinicopathologic features are uncertain. To elucidate them, GA-CCDs exhibiting pepsinogen-I expression (10 lesions: Group A) and randomly selected gastric adenocarcinomas of differentiated type (111 lesions: Group B) were evaluated in this study. Cell differentiation by MUC2, MUC5A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
294
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(319 citation statements)
references
References 18 publications
22
294
2
1
Order By: Relevance
“…A female predominance in nonfamilial FGPs suggests that hormones play a role in the development of FGPs [9] . Some reports have described sporadic FGPs with low-grade or high-grade dysplasia [10,11] and adenocarcinoma [3,4,6] . There are no reports of gastric signet ring cell carcinoma arising from sporadic FGPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A female predominance in nonfamilial FGPs suggests that hormones play a role in the development of FGPs [9] . Some reports have described sporadic FGPs with low-grade or high-grade dysplasia [10,11] and adenocarcinoma [3,4,6] . There are no reports of gastric signet ring cell carcinoma arising from sporadic FGPs.…”
Section: Discussionmentioning
confidence: 99%
“…However, gastric FGPs, which are the most common lesions, have typically been considered benign lesions with no risk 18045 December 21, 2014|Volume 20|Issue 47| WJG|www.wjgnet.com of malignant transformation. Sporadic FGPs are the most common type of gastric polyps that are found during upper endoscopy [6] . The prevalence of FGPs appears to be increasing due to the increased use of upper endoscopy, increased use of acid suppressive medications, and decreased prevalence of H. pylori infection [2] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric adenocarcinoma of fundic gland type (chief cell predominant type) frequently develops in the upper part of the stomach in older patients [9] . Endoscopic finding of gastric adenocarcinoma of fundic gland (chief cell predominant) type may appear to be submucosal tumor-like (60%) or flat or depressed (40%); have a whitish hue (70%); dilated vessels with branching architecture on the surface (50%) with non-atrophic surrounding mucosa (90%) [15] .…”
Section: Discussionmentioning
confidence: 99%
“…A case of gastric adenocarcinoma with chief cell differentiation was first reported by Tsukamoto, et al in 2007 [8] . Ueyama, et al reported ten cases and proposed gastric adenocarcinoma of fundic gland (chief cell predominant type) as a new entity of gastric adenocarcinoma [9] . Gastric adenocarcinoma of fundic gland (chief cell predominant type) is defined as a neoplasm that mainly consists of highly differentiated columnar epithelial cells resembling the fundic gland cells, mainly chief cells, with nuclear atypia.…”
Section: Introductionmentioning
confidence: 99%